Sudden Cardiac Death In Young Age, What Should We Know? - Rochmawati, Icmi Dian; Rizal, Ardian; Putri, Valerinna Yogibuana Swastika; Prasetya, Indra (Universitas Brawijaya, 2024)
While young sudden cardiac death (SCD) is statistically uncommon, its dramatic presentation and the impact it has on families and communities make it a newsworthy issue. Nonetheless, it is important to view SCD in children and adolescents as a public health concern and devise strategies based on research and consensus to address it. Both individuals with and without a history of cardiovascular illness are susceptible to sudden cardiac death. Employing cardiovascular disease risk screening for healthy individuals and those with a family history of sudden cardiac death can serve as a preventive approach against sudden cardiac death. Assessing the severity of cardiovascular disease in people becomes essential in order to prevent disease progression and minimize the risk of mortality from cardiovascular conditions.